Diagnostically important muscle pathology in DNAJB6 mutated LGMD1D - Sandell, Satu (Acta Neuropathol Commun, 2016)
INTRODUCTION: Limb girdle muscular dystrophies are a large group of both dominantly and recessively inherited muscle diseases. LGMD1D is caused by mutated DNAJB6 and the molecular pathogenesis is mediated by defective chaperonal function leading to impaired handling of misfolded proteins which normally would be degraded. Here we aim to clarify muscle pathology of LGMD1D in order to facilitate diagnostic accuracy. After following six Finnish LGMD1D families, we analysed 21 muscle biopsies obtained from 15 patients at different time points after the onset of symptoms. All biopsies were obtained from the lower limb muscles and processed for routine histochemistry, extensive immunohistochemistry and electron microscopy. RESULTS: Histopathological findings were myopathic or dystrophic combined with rimmed vacuolar pathology, and small myofibrillar aggregates. These myofibrillar inclusions contained abnormal accumulation of a number of proteins such as myotilin, αB-crystallin and desmin on immunohistochemistry, and showed extensive myofibrillar disorganization with excess of Z-disk material on ultrastructure. Later in the disease process the rimmed vacuolar pathology dominated with rare cases of pronounced larger pleomorphic myofibrillar aggregates. The rimmed vacuoles were reactive for several markers of defect autophagy such as ubiquitin, TDP-43, p62 and SMI-31. CONCLUSIONS: Since DNAJB6 is known to interact with members of the chaperone assisted selective autophagy complex (CASA), including BAG3 – a known myofibrillar myopathy causing gene, the molecular muscle pathology is apparently mediated through impaired functions of CASA and possibly other complexes needed for the maintenance of the Z-disk and sarcomeric structures. The corresponding findings on histopathology offer clues for the diagnosis.